Accessibility assessment of violations on the stack overflow platform - da Silva, Ingrid M. Miranda; Teran, Luciano Arruda; Mota, Marcelle Pereira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2022: Anais do XXI Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2022)
Accessibility ensures that individuals with disabilities or reduced mobility are equally included in all means with independence, where access to content on the internet is just one of the possible scenarios. Assuming this plurality of people, there are still few well-established techniques that provide manners on developing technologies capable of serving this public. In this way, the Stack Overflow was chosen for being an open and free platform worldwide that aims to add, from doubts, several answers related to web technologies, such as HTML and CSS. Mining its database known as SOTorrent, it was possible to verify whether the recommendations of the Web Content Accessibility Guidelines 2.0, chosen for being more consolidated, are followed or not, besides possible violations. Since the results were taken in a total of 279 snippets that were checked, 597 failures according to WCAG were found, representing a lack of visibility on implementing accessible systems.